Single parents in transformation - Šabdenova, Ajžan Bazarhanovna (Teorija in praksa, 2018)
This study presents social research based on analysis of different aspects in everyday life of single-parent families living in Almaty (Kazakhstan). The authors focus on a model of this family type in terms of its social and economic adaptation, explaining how a single parent can organise and combine family life and child raising with his/her work parallel to achieving the economic independence of his/her family. The article presents the findings of a study on lifestyles in single-parent families, strategies for their survival, and problems related to the transition to a market economy. In addition to several typical reasons for the emergence of single-parent families, which largely include divorces, the unwillingness of partners to start a family, and planned pregnancies for the purpose of giving birth to children outside of marriage, one should note the phenomenon of unofficial marriages, which are entered into only as part of a religious rite. This phenomenon is typical of Kazakhstan. Studies consistently demonstrate that single mothers are in quite an unfavourable economic situation, which is aggravated in social terms by the current economic in Kazakhstan. Extended families and informal social ties are the most important source of economic, emotional and psychological support for this type of family in Kazakhstan.
Keywords: Družina; enostarševske družine; Everyday life; Family; Lifestyles; Parenthood; Starševstvo; Vsakdanje življenje; Življenjski stili